A Religious Media Revolution? The Syrian Conflict and Mediated Sunni Authority - Skovgaard-Petersen, Jakob (Politik, 2016)
This article is a preliminary survey of the media usage of Sunni religious actors during the Syrian conflict. It traces the adoption of new media by religious actors, and analyses the kind of authority these actors have sought to embody, whether regime supporting, oppositional or jihadist. It argues that the conflict has completely altered the means and modes of Sunni religious communication, transforming classical genres and bypassing them with new ones. It concludes that the lack of formal authority in the messaging of the jihadist groupings, and their failed efforts to build up credible religious leaders, is a weakness that could well be exploited in the period to come.